Memory and Forgetting in Lisa Appignanesi’S the Memory Man - Drewniak, Dagmara (Studia Anglica Posnaniensia, 2013)
The aim of this paper is to look at Lisa Appignanesi’s novel The memory man ([2004] 2005), which won the 2005 Holocaust Literature Award, and examine the patterns of remembering and forgetting as indispensable aspects conducive to the formation of Jewish identity. The main character of the book, Bruno Lind, a Holocaust survivor and a scientist dealing professionally with the complicated neurological issues of remembering and losing memory, tries to recollect his war memories during a journey to the places of his youth which are at the same time the sites of his and his family’s trauma. The Holocaust, change of identities, the war memories and finally the stay at the DP camps and escape to Canada return to Bruno Lind’s mind in order to be passed onto the next generation and remembered. This article shows Appignanesi’s novel as an important contribution to the discussion on the role of memory in Jewish identity.